Double helices of dissymmetrical α, α′-disubstituted tripyrrins. Issue 6 (12th January 2023) - Fukuda, Yui; Akamatsu, Yuki; Umetani, Masataka; Kise, Koki; Kato, Kenichi; Osuka, Atsuhiro; Tanaka, Takayuki
Abstract : Dissymmetrical α, α′-disubstituted tripyrrins have been prepared using a modified synthetic protocol. Abstract : Dissymmetrical α, α′-disubstituted tripyrrins have been prepared using a modified synthetic protocol. Tripyrrin 2a bearing 3, 5-bis(trifluoromethyl)phenyl and 4-methoxyphenyl moieties showed an anti -type dimer arrangement in the solid state. In contrast, syn -type dimers were observed for tripyrrin 2b bearing 3, 5-bis(trifluoromethyl)phenyl and 3, 5-di- t -butylphenyl moieties. In addition, proton-exchange NH tautomerization was observed in 2b .